PENGARUH AUDIT TENURE, OPINI AUDIT GOING CONCERN, PERGANTIAN MANAJEMEN DAN AUDIT DELAY TERHADAP AUDITOR SWITCHING DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - M. Isa Alamsyahbana; Hendy Satria; Klaudia, Klaudia; Bambang Sambodo (Juremi: Jurnal Riset Ekonomi, 2024)
The purpose of this research is to find out whether there is an effect of audit tenure, going concern audit opinion, management change and audit delay on auditor switching, and whether firm size is able to moderate the independent variables on the dependent variable.The method used in this research is a quantitative method. The research object is Consumer Cyclicals Sector companies listed on the IDX for the 2018-2021 period. For the population in this study, there were 132 companies and the samples obtained after using the purposive sampling method were 25 selected companies. The data analysis technique in this study used the logistic regression method by utilizing SPSS as a data processing application.The results of this study indicate that audit tenure has no effect on auditor switching, going concern audit opinion has no effect on auditor switching, management change has no effect on auditor switching, and audit delay has a positive effect on auditor switching. Firm size variable as a moderating variable is not able to moderate audit tenure, going concern audit opinion and management changes to auditor switching and is only able to moderate audit delay to auditor switching